Log in to add a comment

## Answers

1. 5x - y = 7

x = 2

y = 3

5(2) - 3

10 - 3

= 7

2. -3x - 2y = 12

x = 2

y = 3

-3(2) - 2(3)

-6 - 6

= -12

x = 2

y = 3

5(2) - 3

10 - 3

= 7

2. -3x - 2y = 12

x = 2

y = 3

-3(2) - 2(3)

-6 - 6

= -12

The Brainliest Answer!

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Using substitution method to get the answer provided by Awesome Helper (and I hope that this solution stays here. Thank you.)

Equation 1) 5x - y = 7

Equation 2) - 3x - 2y = -12

Step 1, using Equation 1

5x - y = 7

-y = -5x + 7

y = 5x - 7

Equation 3: y = 5x - 7

Step 2: Using Equation 2, substitute 5x-7 for y

-3x - 2y = -12

-3x - 2 (5x - 7) = -12

- 3x - 10x + 14 = -12

-13x = -12 - 14

-13 -13

x = 2

Step 3, Using Equation 3, substitute 2 for x

y = 5x - 7

y = 5 (2) - 7

y = 10 - 7

y = 3

The solution to this system is x = 2; y = 3

Equation 1) 5x - y = 7

Equation 2) - 3x - 2y = -12

Step 1, using Equation 1

5x - y = 7

-y = -5x + 7

y = 5x - 7

Equation 3: y = 5x - 7

Step 2: Using Equation 2, substitute 5x-7 for y

-3x - 2y = -12

-3x - 2 (5x - 7) = -12

- 3x - 10x + 14 = -12

-13x = -12 - 14

__-13x__=__-26__-13 -13

x = 2

Step 3, Using Equation 3, substitute 2 for x

y = 5x - 7

y = 5 (2) - 7

y = 10 - 7

y = 3

The solution to this system is x = 2; y = 3